ChemInform Abstract: Acylsilanes in Iridium‐Catalyzed Directed Amidation Reactions and Formation of Heterocycles via Siloxycarbenes. Issue 17 (April 2016) - Becker, Peter; Pirwerdjan, Ramona; Bolm, Carsten
Abstract: A highly efficient ortho‐amidation of aroylsilanes with sulfonyl azides is developed.